Strategies for Dengue Control in Urban Areas of Lima: An Incidence Study in South Lima and North Lima - Bocanegra Morales, Cristian Omar (2024)
The article examines the issue of dengue within the Peruvian context, with a particular focus on the urban areas of Lima Sur and Lima Norte, regions notable for their high incidence of cases and their significance in the country’s epidemiological landscape. The research employs a mixed methodology, combining quantitative analysis of epidemiological data with qualitative perspectives derived from public health studies. The results reveal a high incidence of dengue in these areas, highlighting the urgent need for more effective measures to control its spread.The study utilizes quantitative data on dengue incidence and prevalence, obtained from health records and epidemiological reports, and conducts a qualitative analysis to identify the environmental, socioeconomic, and health-related factors contributing to the disease’s spread. Factors such as limited access to basic services and environmental conditions conducive to mosquito vector proliferation are emphasized.Additionally, the article proposes the implementation of advanced technologies, such as chatbots, through a strategic approach based on the theory of change. This approach aims not only to mitigate the spread of dengue through early diagnosis and community education but also to improve the quality of life for affected communities. The integration of these technologies is intended to optimize the health system’s response, reduce the burden on traditional medical services, and promote a more effective and sustainable management of the disease.